Characteristics of transplant athletes competing at national and international transplant games. Issue 1 (28th February 2022) - Hames, Thomas; Leddington-Wright, Sheila; Thake, Charles Douglas; Price, Mike
Abstract : Objective: To describe the characteristics of athletes with solid-organ transplants (TxA) attending the British and World Transplant Games. Methods: 220 TxA completed an online survey to explore transplant history, medications, training advice and support and limitations to training. Results: TxA were predominantly caucasian, male, kidney recipients in their mid-forties and approximately 11 years post-transplant. The majority of TxA took some form of medication (immunosuppressants 88%, steroids 47%, antihypertensives 47%, statins 28%, antiplatelets 26%, antibiotics/antivirals/antifungals 20%). Stem cell recipients were least likely to require medication. Post-transplant complications were experienced by 40% of TxA, with 53% of these being rejection. Although over half the participants (57%) initially received exercise or training advice post-transplant, only 34% of these received this from their consultants or immediate medical team. Only 1% had been specifically directed towards transplant sport. Half of the TxA (53%) perceived there were limitations preventing them from performing at their potential, 45% considered they did not recover from training as well as non-TxA while 29% felt they trained equally to non-Tx's. Only 6% considered medication impaired training. TxA competed for a range of reasons from social and health benefits to winning medals. Conclusions: TxA compete at the British and World Transplant Games for a diverse range of reasons. Athletes manage a range of medications with a range of exercise and health experiences pre-transplant. TxA face a lack of both general and specific exercise training and recovery guidance. The individuality of each TxA's background should be considered and is likely reflected in their exercise capacity and goals.